Cover Feature: Effect of Vapor‐phase‐treatment to CuZnZr Catalyst on the Reaction Behaviors in CO2 Hydrogenation into Methanol (ChemCatChem 5/2019). Issue 5 (22nd February 2019) - Chen, Shuyao; Zhang, Junfeng; Wang, Peng; Wang, Xiaoxing; Song, Faen; Bai, Yunxing; Zhang, Meng; Wu, Yingquan; Xie, Hongjuan; Tan, Yisheng
Abstract : The Cover Feature shows the formation of methanol from CO2 hydrogenation on CuZnZr catalyst. In their Full Paper, S. Chen et al. investigate the reasons that vapor‐phase‐treatment (VPT) leads to the changes in reaction behavior on the catalysts. The VPT with TPABr induces obvious increases in the particles size of CuO, ZnO and ZrO2, promotes the formation of the rod‐like structure, Zn and Zr enrichments on surface and the presence of more concentration of oxygen vacancies. These synergetic effects of the changes in surface properties and morphology restrain the competitive reverse water‐gas shift (RWGS) reaction furthest, subsequently leading to the supremacy of catalyst for methanol selectivity. More information can be found in the Full Paper by S. Chen et al. on page 1448 in Issue 5, 2019 (DOI: 10.1002/cctc.201801988 ).